Sistema informático de control de ingreso y salida de vehículos mediante detección y reconocimiento de placas - López Álava, Frowen Abdón (2019)
This titling work aimed to develop a computer system to control the entry and exit of vehicles by recognizing license plates for the maintenance yard of the GADM of Chone canton; which contributes to improve the control and administration of public resources (vehicles). For the development of the system it was necessary to follow the phases that make up the digital image processing: capture, preprocessing, segmentation, representation, description, and recognition. In the first and second phase, we will obtain and process images of license plates. In the segmentation phase the objects of interest (plate location and characters) which are represented as numerical and understandable data for the computer were separated. In the last phase, the recognition of the characters and digits, which represent the license plates, using computer vision functions, which resulted in the recognition model was carried out. In addition, a user interface was designed to make plate detection simple and fast. The tests of the recognition system showed that it is capable of achieving a 95% global analysis in terms of the plates correctly recognized.